2008
DOI: 10.1158/0008-5472.can-08-1494
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Blockade of Transforming Growth Factor-β Signaling Augments the Efficacy of Immunogene Therapy

Abstract: Locally produced transforming growth factor-B (TGF-B) promotes tumor-induced immunosuppression and contributes to resistance to immunotherapy. This article explores the potential for increased efficacy when combining immunotherapies with TGF-B suppression using the TGF-B type I receptor kinase inhibitor SM16. Adenovirus expressing IFN-B (Ad.IFN-B) was injected intratumorally once in established s.c. AB12 (mesothelioma) and LKR (lung cancer) tumors or intratracheally in a Kras orthotopic lung tumor model. Mice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 52 publications
(64 reference statements)
5
67
1
Order By: Relevance
“…Taken together, these results demonstrate that SB-431542 can induce potent phenotypic and functional maturation of murine and human DCs. Although we can find several studies of the immunological therapeutic effect of TGFß blocking (39,40), this is the first published study in which a small-molecule inhibitor of the TGFß receptor triggers maturation of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results demonstrate that SB-431542 can induce potent phenotypic and functional maturation of murine and human DCs. Although we can find several studies of the immunological therapeutic effect of TGFß blocking (39,40), this is the first published study in which a small-molecule inhibitor of the TGFß receptor triggers maturation of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that TGF-b inhibitors will have their most important therapeutic activity in cancer through effects on the TME, particularly, but not only, in neutralizing or reversing immune suppression. Indeed, the combination of TGF-b inhibition together with existing immunotherapies, such as cancer vaccines (Jia et al 2005;Nemunaitis and Murray 2006;Kim et al 2008), adoptive Tcell transfer Wallace et al 2008), chimeric antigen receptor T-cell therapy (Gill and June 2015;Wu et al 2015), and immune checkpoint blockade (Topalian et al 2012;Lipson et al 2013), will likely provide the major basis of their therapeutic usage. Here again, the major players appear to be TGF-b1 and -b2.…”
Section: Potential Oncology Applications For Tgf-b Blockadementioning
confidence: 99%
“…However, another study showed that TGFβ reduces the expression of the adhesion molecule L-Selectin, resulting in impaired neutrophil recruitment to sites of inflammation [86]. Blockage of TGFβ signaling increased the numbers of neutrophils in tumors, which was associated with increased amount of chemokines and cytokines within the tumor, concomitant with increased ICAM-1 expression on endothelial cells [13,90]. The increase in intra-tumor neutrophil number observed following anti-TGFβ signaling therapy can be explained by the ability of TGFβ to inhibit endothelial adhesiveness of neutrophils and neutrophil transmigration in vivo [91].…”
Section: Tgfβmentioning
confidence: 99%